2021
DOI: 10.3390/su131810377
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties and a Multiple Indicators Multiple Cause Model of the Career Aspiration Scale with College Students of Rural Thailand

Abstract: To help address educational inequalities in student backgrounds and career plans, the measurement of career aspirations can provide crucial information about inequality related to career opportunities. Therefore, this study analyzed the factor structure and psychometric properties of the Career Aspiration Scale-Revised (CAS-R) and the effects of sociodemographic variables on the CAS-R. The study participants were 590 undergraduates at three community colleges in rural Thailand. Confirmatory factor analysis (CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
(90 reference statements)
0
9
0
Order By: Relevance
“…Support for the reliability of the total score has been found with populations of US women employed in higher education (α = .91; Gregor et al, 2021) and demonstrated validity (in its relation to achievement motivation, work role salience, and willingness to compromise career for future family in theoretically predicted ways; Gregor & O’Brien, 2016). The psychometric properties and factor structure of the CAS-R have been analysed in non-Western student populations including Korean undergraduate women (Kim et al, 2016) and Thai undergraduate students (Kunchai et al, 2021). In the current study the Cronbach’s alpha for the total score on the CAS-R was .90.…”
Section: Methodsmentioning
confidence: 99%
“…Support for the reliability of the total score has been found with populations of US women employed in higher education (α = .91; Gregor et al, 2021) and demonstrated validity (in its relation to achievement motivation, work role salience, and willingness to compromise career for future family in theoretically predicted ways; Gregor & O’Brien, 2016). The psychometric properties and factor structure of the CAS-R have been analysed in non-Western student populations including Korean undergraduate women (Kim et al, 2016) and Thai undergraduate students (Kunchai et al, 2021). In the current study the Cronbach’s alpha for the total score on the CAS-R was .90.…”
Section: Methodsmentioning
confidence: 99%
“…To simplify the data interpretation process, the five resulting components are presented using the mean values. The mean values are grouped into five categories, namely, strongly disagree (1.00–1.80), do not agree (1.81–2.0), neutral (2.61–3.40), agree (3.41–4.20), and strongly agree (4.21–5:00) [ 55 , 56 , 57 ]. This shows that the higher the mean value, the higher the number of respondents who agree with the statement of one component.…”
Section: Methodsmentioning
confidence: 99%
“…Achievement goal orientation refers to one's inspiration to engage in activities geared toward achieving goals that will lead him or her to develop behaviors or mindsets [28,29] or focusing on motivation toward qualitatively different abilities relevant to outcomes and chance of learning [30][31][32][33]. Therefore, it is used as a tool to specify criteria for target behavior and as a feedback mechanism to improve the target behavior and engage in self-monitoring [23].…”
Section: A Achievement Goal Orientation Scalementioning
confidence: 99%